Health Promotion Program on Students' Healthy Living Behavior - Widiyanto, Aris (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2025)
Health promotion programs in higher education aim to increase awareness and shape healthy living behaviors among students. Measuring the effectiveness of these programs is important to determine the extent to which these programs are able to influence student behavior. Objectives: The aim of the study was to analyze the effectiveness of health promotion programs on students' healthy living behavior. Methods: This study used a descriptive design. The study population was students who were studying in the health sector in Surakarta City. The total sample in this study was 100 respondents, who were selected using purposive sampling technique. Inclusion criteria include active students of health study programs, willing to become respondents, and have participated in health promotion programs. The dependent variable in this study was students' healthy living behavior, while the independent variable was the health promotion program. Data was analyzed accordingly. Results: the data showed that majority of participants rarely ate healthy (80%), had sufficient exercise (71%), and lacked sleep (60%). The overall effectiveness of the program was rated as adequate by majority of respondents (66%). Conclusion: The health promotion program is quite effective in improving healthy sleep behavior, but needs to be improved on healthy food consumption and physical activity.